Description of Vaginal Laxity and Prolapse and Correlation With Sexual Function (DeVeLoPS). Issue 6 (8th October 2021) - Polland, Allison; Duong, Vi; Furuya, Rachel; Fitzgerald, Jocelyn J.; Wang, Haijun; Iwamoto, Aya; Bradley, Sarah; Iglesia, Cheryl B.
Abstract: Introduction: Vaginal laxity (VL) is a sensation of vaginal looseness which may develop after pregnancy and vaginal delivery and may be affected by prior pelvic surgery, menopause and aging. Pelvic organ prolapse (POP) is a disorder in which pelvic organs descend from the normal position. VL has attracted recent attention due to the advent of energy-based treatments for this symptom. Aim: To determine the correlation between VL symptoms and physical exam findings of POP, specifically the introital measurement of genital hiatus. Methods: This was a multi-center cross-sectional study of sexually active women over 18 years of age with a parity of one or greater. Subjects completed the Vaginal Laxity Questionnaire (VLQ), the Pelvic Floor Distress Inventory-20, and the Female Sexual Function Index (FSFI), and were asked if a sexual partner had commented on laxity. Subjects underwent pelvic exam, including the pelvic organ prolapse quantification (POP-Q). Main Outcomes Measures: Correlation between VL symptoms as measured by the VLQ and POP as measured by elements of the POP-Q. Results: A total of 95 subjects with an average age was 54.3 ± 13.18 years were included. Sixty-three percent of patients were postmenopausal. The average VLQ score was 4.2 ± 1.35 and the average FSFI score was 23.42 out of 36. There was no significant correlation between VLQ score and POP or mid-vaginal caliber. Sensation of vaginal tightness was significantly associated with age ( P =0.03) and menopausal status ( P =0.04). Only 28% of partners commented on laxity and the majority commented on the vagina being tight (21%) rather than loose (7%). Conclusion: VL was not correlated with physical exam findings quantifying POP or sexual function. This study emphasizes the need to develop a more standardized definition of VL and a better assessment tool for VL symptoms.